Large-scale grid computing approaches towards mapping the conformational space of mycolic acids from Mycobacterium tuberculosis - Meletiou, Athina (2018)
Tuberculosis (TB) has plagued humanity for centuries, and, despite being largely curable, it still claims thousands of lives daily. The causative agent, Mycobacterium tuberculosis (M. tb), shows resilience by evading immunological and antitubercular challenges. This is mainly due to its lipid-rich cell wall, whose main components are mycolic acids (MAs). MAs are long fatty acids with functional groups of precise stereochemistry. The MA chemical structure and composition balance in the cell wall modulates antigenicity, cell wall permeability, and virulence. MA chemical structure also steers MA folding. However, MA structure-function relationships are still not fully understood.